2006
DOI: 10.1186/1472-6920-6-45
|View full text |Cite
|
Sign up to set email alerts
|

On line clinical reasoning assessment with Script Concordance test in urology: results of a French pilot study

Abstract: Background: The Script Concordance test (SC) test is an assessment tool that measures the capacity to solve ill-defined problems, that is, reasoning in a context of uncertainty. This study assesses the feasibility, reliability and validity of the SC test made available on the Web to French urologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 24 publications
(52 reference statements)
2
42
0
3
Order By: Relevance
“…Although the present study is limited in several ways, our results are well correlated with other studies on Concordance test which have previously demonstrated the validity and the reliability on the Concordance test in different medical specialties (Brailovsky et al 2001;Charlin et al 2002;Charlin & Van der Vleuten 2004;Gagnon et al 2006;Sibert et al 2006b;Charlin et al 2007;Meterissian et al 2007). Sample size of participants was comparable or greater than those reported in the literature.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Although the present study is limited in several ways, our results are well correlated with other studies on Concordance test which have previously demonstrated the validity and the reliability on the Concordance test in different medical specialties (Brailovsky et al 2001;Charlin et al 2002;Charlin & Van der Vleuten 2004;Gagnon et al 2006;Sibert et al 2006b;Charlin et al 2007;Meterissian et al 2007). Sample size of participants was comparable or greater than those reported in the literature.…”
Section: Discussionsupporting
confidence: 80%
“…The evaluation system can be assessed via any computer system with a standard Web browser. Contrary to the Concordance test in urology, which was limited to French urologists (Sibert et al 2006b), the concordance test in therapeutics was open to any members of the APNET and any students or trainees from medical schools members of the FMVU consortium. The home page of the test (Figure 1) (Sibert et al 2006), most of the participants primarily came from 'Ile de France' area (N ¼ 125) and from 'Normandy' geographical area (N ¼ 75); the other participants (N ¼ 51) came from various French areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The instrument has been developed in various educational settings and in different countries and languages and is based on written presentation of short clinical cases, followed by a choice of diagnostic and therapeutic decisions. 1,[5][6][7][8][9][10][11][12][13] Routine use of the SCT is not common in Brazilian universities.…”
Section: Introductionmentioning
confidence: 99%
“…On a notamment pu mettre en évidence une progression des scores selon qu'il est administré respectivement à des étudiants en méde-cine, à des internes et à des praticiens expérimen-tés [4][5][6][7][8] . Les modalités techniques de construction et d'administration d'un test sont également bien connues [9][10][11][12][13][14] .…”
Section: Introductionunclassified